2018
DOI: 10.4103/ajts.ajts_29_17
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bedside transfusion practices at a tertiary care center: A step closer to controlling the chaos

Abstract: BACKGROUND:Blood transfusion chain can be divided into three phases: preanalytical (patient bedside), analytical (steps done at transfusion services), and postanalytical (bedside). Majority (~70%) of events due to blood transfusion have been attributed to errors in bedside blood administration practices. Survey of bedside transfusion practices (pre-analytical and post analytical phase) was done to assess awareness and compliance to guidelines regarding requisition and administration of blood components.MATERIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
(20 reference statements)
3
19
0
3
Order By: Relevance
“…In this study, 24%–35% of the participants knew the right issues to discuss whilst obtaining informed consent for blood transfusion ( Table 2 ). A previous observational prospective study similarly found that 72% of the participants did not obtain informed consent from the patients and family before initiating blood transfusion [ 17 ]. Another observational study of two tertiary hospitals in Nepal also found that 2.4%–8.2% of 86 observations of blood transfusions done involved informing patients and family of reasons for transfusion, benefits, and potential risks whilst seeking informed consent to transfuse [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 24%–35% of the participants knew the right issues to discuss whilst obtaining informed consent for blood transfusion ( Table 2 ). A previous observational prospective study similarly found that 72% of the participants did not obtain informed consent from the patients and family before initiating blood transfusion [ 17 ]. Another observational study of two tertiary hospitals in Nepal also found that 2.4%–8.2% of 86 observations of blood transfusions done involved informing patients and family of reasons for transfusion, benefits, and potential risks whilst seeking informed consent to transfuse [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Khetan et al . reported lack of awareness regarding guidelines, improper sampling practices and lack of technology to be the major contributing factor in bedside errors.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various wards, maximum errors occurred in emergency wards. This could be clearly explained by the increased work load and [23] reported lack of awareness regarding guidelines, improper sampling practices and lack of technology to be the major contributing factor in bedside errors.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to control and increase the safety of the patient during transfusion practice and analysis of the main critical points that allow the error [14]. Therefore, the advancement of public policies, clinical guidelines and standard procedures with updated approaches in blood transfusion practices and internal audits are necessary to analyze the conditions of care and the implementation of standards [13,23]. These events direct the professionals to perform new researches which aim at improving evidence regarding patient safety and quality of care [14].…”
Section: Patient Safety and Risk Managementmentioning
confidence: 99%